Guarapiranga and Burle Marx Parks: Perception and Use By Regulars, São Paulo City, Brazil - Brito, Edmilson Nazareno; Nascimento, Ana Paula Branco do (Revista Nacional de Gerenciamento de Cidades, 2021)
Studies on the population’s perception towards urban green areas can contribute to the management of these spaces. This study analyzed the perception and use of two urban parks by their regulars. The regulars’ individual characteristics were identified and categorized according to the activities taking place in the parks, in order to characterize the uses that the population makes of these spaces. The data survey was accomplished by means of 103 interviews in each park, following a structured guideline that allowed the quantitative analysis of the data thus obtained. These parks are perceived and used for providing social and environmental functions, besides leisure and health benefits, thus contributing to the quality of life. The basic infrastructure, such as toilets and drinking fountains, and physical exercise facilities, such as multisport courts, playgrounds and hiking trails, are perceived as important for the social life of regulars of various age groups.